GENETIC VARIABILITY AND CHARACTER ASSOCIATION STUDIES IN CHICKPEA (Cicer arietinum L.) WITH SPECIAL REFERENCE TO TRAITS AMENABLE TO COMBINE HARVESTING - V. JAYALAKSHMI*, A. TRIVIKRAMA REDDY, B. VISHNU; M. MOHAMMED IMRAN (The Journal of Research ANGRAU, 2020)
The study was taken up with 100 advance chickpea breeding lines obtained from different institutes during Rabi, 2016-17 to assess the genetic variability and character association for traits contributing to combine harvesting. Two advance breeding lines-NBeG 864 (3.1 t ha-1) and NBeG 862 (2.7 t ha-1) which had the first pod bearing node 30 cm from above the ground; plant height greater than 50 cm and angle 60°or above between the main axis and primary branch with significant yield advantage over machine harvestable check cultivar ‘HC 5’ were identified. Genetic variability as measured in terms of phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV) was moderate for height of the first pod and low for angle of the primary branch and plant height. Yield attributing traits viz., number of primary branches, number of secondary branches, 100 seed weight, shoot biomass and days to 50 per cent flowering exhibited moderate PCV and GCV values. Height of the first pod, days to 50 per cent flowering and 100 seed weight exhibited high heritability and high genetic advance indicating the scope for genetic improvement of the traits through phenotypic selection. Character association studies revealed shoot biomass as a major contributing character for seed yield in chickpea. Plant height and height of the first pod exhibited a strong positive association between themselves and with shoot biomass. Also, inter se correlations among the positively associated traits with seed yield viz.,100 seed weight, number of secondary branches and plant height with shoot biomass showed significance in breeding genotype s suitable for combine harvesting.